Cognitive predictors of oral reading miscues in the text reading process in a transparent orthography: Working memory and visual retention - Kocaarslan, Mustafa; Erden-Kocaarslan, Gulcan (Springer, 2023)
Cognitive factors beyond linguistic skills that cause readers to produce oral reading miscues while reading text have not yet been adequately examined. This study focuses on oral reading miscues produced by third grade Turkish students (n = 110) in Turkish, which has a transparent orthography, and aims to reveal the role of certain cognitive factors in this process. Accordingly, after controlling for reading speed, the role of working memory, sustained attention, and visual short-term memory in explaining oral reading miscues in passages was investigated. As a result of the study, after taking reading speed into consideration, it was determined that working memory, sustained attention and visual short-term memory significantly predicted oral reading miscues and explained 25% of the variance. Working memory emerged as the strongest predictor. These findings are important in terms of revealing the multi-layered structure of the concept of oral reading fluency and its relationship with higher-order cognitive skills. Finally, it is recommended that intervention studies aimed at improving reading fluency take domain-general skills into account.
Keywords: Oral Reading Miscues; Working Memory; Sustained Attention; Visual Short-Term Memory